Phishing Detection Methods - Mariusz SZAREK (Communications of International Proceedings, 2021)
The article describes the phishing attack phenomenon, what phishing is, its division and characteristics. Phishing, despite its simplicity, is extremely dangerous and effective - the individual phases of the attack are described along with sample phishing content. Reference was made to the methods and model of phishing identification described in journals and scientific publications. Use expert knowledge when analysing technical and non-technical phishing indicators - which can be difficult to analyse and detect automatically. The economic costs of acquiring an expert may be significant and unattainable for many micro-enterprises - the phishing detection model proposed in the article assumes the construction of an expert system and equipping it with rules and data - expert knowledge. The concept of a mechanism that combines the capabilities of neural networks to detect and analyse phishing together with the rules of an expert system is a promising method of detection and defence against phishing.
Keywords: Cybersecurity; Phishing; Machine Learning; Expert System.